A new cinnamaldehyde-rhodamine based dual chemosensor for Cu²⁺ and Fe³⁺ and its applicability in live cell imaging - Nur Amira Solehah Pungut; Tan, Chun Hoe; Hazwani Mat Saad; Sim, Kae Shin; Tiong, Sheena Yin Xin; Ang, Chee Wei; Gan, Chun Hau; Kong, Kien Voon; Tan, Kong Wai (Elsevier B.V., 2022)
A new fluorescent sensor, RT4 has been synthesized by reacting trans-4-(diethylamino)cinnamaldehyde with rhodamine B hydrazide in a one-step reaction. The characterization of RT4 was done by using FT-IR, 1 H NMR, 13C NMR, and single crystal X-ray crystallography. In aqueous acetonitrile (1:1, v/v pH 7.5), RT4 exhibited a highly selective and sensitive colorimetric response upon recognition of Cu2+ and fluorometric response with Fe³⁺ ions. The calculated limit of detections (LOD) of RT4 with Cu²⁺ and Fe³⁺ were 0.20 and 0.18 µM at λabs/em = 555 and 585 nm, respectively. Test strips for colorimetric detection of Cu²⁺ and Fe³⁺ as an on-site test kit were successfully prepared. Furthermore, the MTT assay indicated that RT4 possess low cytotoxicity in human colorectal carcinoma HCT 116 after 24 h. The fluorescence microscopy experiment suggested that RT4 could also serve as a biological fluorescence probe for the detection of Fe³⁺in HCT 116 cells.